The case of self‐resolving type III achalasia after bilateral lung transplant. Issue 7 (16th March 2017) - Aggarwal, P.; Bansal, V.; Aggarwal, N.; Arora, Z.; Murthy, S.; Gabbard, S.
Abstract: Background: Post‐surgical achalasia has been previously described in large case series but there are limited data on the natural progression of the disease process. In general, achalasia is considered an "incurable" disease as per published guidelines. We present here, the first report of a patient with post‐surgical achalasia which resolved spontaneously. Methods: This is a retrospective chart review. Key Results: A 60‐year‐old male presented for dysphagia 3 months status post‐bilateral lung transplant and was diagnosed with achalasia following positive manometry. Absent any treatment, his repeat manometry showed complete, spontaneous resolution of the achalasia 2 years following lung transplant. Conclusions & Inferences: To our knowledge, this is the first such case of spontaneously resolving achalasia following bilateral lung transplant. This case warrants further study in to the natural progression of post‐surgical achalasia. Abstract : Achalasia is generally considered to be an incurable disease as per the published guidelines. We present here, the first report of a patient with post‐surgical achalasia which resolved spontaneously. This case supports the hypothesis that post‐surgical or post‐traumatic achalasia may represent a different entity.